The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fpsyt.2021.611108
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health, Culture and Resilience—Approaching the COVID-19 Pandemic From a South African Perspective

Abstract: It is understandable that the challenges of living through a severe contagious outbreak, like the coronavirus disease 2019 (COVID-19), cannot be tolerated for long and that some individuals may require emotional, psychological, and spiritual support in order to strengthen their resilience to navigate this difficult period. As clinicians and researchers in the field of mental health, we need to appreciate the roles that culture, spirituality, and religion play in comforting people who survive such an outbreak a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 25 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…Stress at an early stage of working life can contribute to burnout, depression, and unfavorable work outcomes in later life, depending on the life course perspective [ 14 , 15 ]. Various psychosocial interventions have been suggested to overcome stress, such as relaxation, mindfulness practices, or social engagement, ideally performed in groups [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Stress at an early stage of working life can contribute to burnout, depression, and unfavorable work outcomes in later life, depending on the life course perspective [ 14 , 15 ]. Various psychosocial interventions have been suggested to overcome stress, such as relaxation, mindfulness practices, or social engagement, ideally performed in groups [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, when social isolation increases adult psychological distress and precipitates anger (Brooks et al, 2020). Moreover, as in this study, space proximity with confinement to an overcrowded house may have triggered adult stress responses (Mashaphu et al, 2021;Russell et al, 2020). Children are at risk of psychological maladjustment when parents cannot attend to children's physical, emotional and schooling needs (Maree, 2021;Thibodeau-Nielsen et al, 2021).…”
Section: Discussionmentioning
confidence: 59%
“…Likewise, Ting et al (2021) found that cultural responses and religious beliefs moderate everyday stress and major life crises such as the effects of the pandemic. Similarly, religious and cultural events in South Africa lie at the heart of communities’ social systems and contribute to a sense of connectedness and belonging ( Mashaphu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Social capital is intrinsically linked to the resilience of individuals and communities and the two dimensions mutually influence each other. The response to Covid has determined interesting phenomena of resilience in low-income countries and there are studies, especially conducted in Africa, that show the connections between Covid, vulnerability and resilience ( 61 64 ).…”
Section: The Sources Of Health Disparities and The Mental Health Care...mentioning
confidence: 99%